Relationship between factors of teachers’ leadership: Positive attitudes, professional activeness, and stress at school - Lina Kaminskienė; Vilma Žydžiūnaitė; Rūta Juozaitienė (Management : Journal of Contemporary Management Issues, 2021)
Today, the traditional role of teachers is challenged, and teaching practice requires less time for face-to-face instruction, a unique position that does not impose responsibilities on one person (teacher or student) and creates a common teaching and learning space in which new knowledge is co-created and socially developed. This change requires teachers’ high professionalism and leadership skills, which is the key component of a successful educational process. Therefore, it is important for researchers, school principals, and teachers to understand better the predictive factors of teachers’ leadership, which should be developed, nurtured, and sustained. This study addresses the teachers’ leadership regarding their attitudes toward themselves, attitudes towards the school, teachers’ activeness, and stress experienced at school. The study involved 418 teachers from five regions in Lithuania. The findings indicate that the four analyzed factors, influencing teacher leadership are strongly interrelated. Moreover, the research results reveal determinants surrounding the factors of interest, which leads to a more complex understanding of underlying reasons and problems related to practicing teachers’ leadership at school.